Legal Protection of CBT Workers in Terms of Wages: A Case Study in Bedah Menoreh Pathway - Bima Setya Nugraha; Ari Hernawan; Linda Yanti Sulistiawati (Journal of Indonesian Tourism and Development Studies, 2021)
One of the most vital industries with significant potential for development in Indonesia is the tourism industry. The current trend of the tourism industry development tends to lean towards Community-Based Tourism or CBT. Thus, the focus of this research is the legal protection of CBT workers, especially in terms of wages at Bedah Menoreh Pathway. This research aimed to collated and analyzed existing models of wages legal protection for CBT workers and compare them with Indonesian laws and regulations pertaining to Bedah Menoreh Tourism Supporting Path development. This research is empirical normative research. Analysis was conducted through systematizing and defining acquired data chronologically and on the basis of forms of legal protection as stated in laws and regulations. Based on the findings and analysis, several factors caused the absence of legal protection of CBT workers especially in terms of wages. The researcher concludes that there must be a new pattern on wages regulation mechanism that will protect tourism workers relative to the condition of this unique CBT Attraction.Keywords: Bedah Menoreh pathway, CBT Worker, legal protection, wages.